Incidence and risk of hepatic toxicities with PD-1 inhibitors in cancer patients: a meta-analysis - Zhang X; Ran Y; Wang K; Zhu Y; Li J (Dove Medical Press, 2016)
Xi Zhang,1 Yuge Ran,1 Kunjie Wang,2 Yuanxue Zhu,2 Jinghua Li3 1Department of Radiation Oncology, 2Department of Medical Oncology, 3Department of Hepatobiliary Surgery, Affiliated Hospital of Hebei University, Baoding, People’s Republic of China Purpose: Anti-programmed cell death receptor-1 (PD-1) antibodies have demonstrated antitumor activity in many cancer entities. Hepatic adverse events (AEs) are one of its major side effects, but the overall risks have not been systematically evaluated. Thus, we conducted this meta-analysis to investigate the overall incidence and risk of developing hepatic AEs in cancer patients treated with PD-1 inhibitors. Methods: PubMed, Embase, and oncology conference proceedings were searched for relevant studies. Eligible studies were randomized controlled trials of cancer patients treated with PD-1 inhibitors with adequate data on hepatic AEs. Results: A total of nine randomized controlled trials with a variety of solid tumors were eligible for the meta-analysis. The use of PD-1 inhibitors significantly increased the risk of developing all-grade hepatic AEs but not for high-grade hepatic AEs in comparison with chemotherapy or everolimus control. Additionally, the risk of all-grade and high-grade hepatic AEs with a nivolumab/ipilimumab combination was substantially higher than ipilimumab. No significant differences in the risk of all-grade and high-grade hepatic AEs were found between PD-1 inhibitors monotherapy and ipilimumab. Conclusion: While the use of PD-1 inhibitors is associated with an increased risk of developing hepatic AEs in cancer patients, this is primarily for lower grade events. Keywords: cancer, hepatic toxicities, PD-1 inhibitors, meta-analysis